Deciphering the Epigenetic Code of Stem Cells Derived From Dental Tissues - Li, Ye; Zhao, Xitong; Sun, Meng; Pei, Dandan; Li, Ang (Frontiers in Dental Medicine, 2022)
Stem cells derived from dental tissues (DSCs) exhibit multipotent regenerative potential in pioneering tissue engineering regimens. The multipotency of DSCs is critically regulated by an intricate range of factors, of which the epigenetic influence is considered vital. To gain a better understanding of how epigenetic alterations are involved in the DSC fate determination, the present review overviews the current knowledge relating to DSC epigenetic modifications, paying special attention to the landscape of epigenetic modifying agents as well as the related signaling pathways in DSC regulation. In addition, insights into the future opportunities of epigenetic targeted therapies mediated by DSCs are discussed to hold promise for the novel therapeutic interventions in future translational medicine.